Enhancing English Learning Achievement through Problem Based Learning: An Action Research at SMAN 1 Jepara - Haryanto Haryanto (IJOTL-TL (Indonesian Journal of Language Teaching and Linguistics))
This research aims to describe the learning achievements of the English Language through Problem Based Learning (PBL) Model. This study used a two cycle-classroom action research as the design and assigned 30 graders of X Science Class of SMAN 1 Mlonggo Jepara Regency in the year 2018/2019.  Each cycle consisted of four stages: planning, implementing, observing, and reflecting. Indicators of success are determined for which the students achieved a minimum 75% of mastery learning after they are exposed to the PBL Model.  The research results show (1) the average learning achievement in the first cycle was 6.92 and in the second cycle the cycle was 8.67; (2) minimum mastery learning in the first cycle was 13 (36.11%) and 23 (63.89%) in the second cycle; and (3) completeness in the classical learning in cycle I was 36.11% and 100.00% in cycle. In addition, the studentsâ€™ participation and motivation after the implementation of PBL increase somewhat 82.4% and of 82.47% studentsâ€™ states strongly agree to the implementation of PBL model.